PERBANDINGAN PENGARUH DOSIS 75% DAN 100% TERHADAP PENURUNAN BERAT SETELAH MELAKUKAN LATIHAN - samodra, touvan Juni (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2021)
The exercise dose needs to be selected to determine the expected results. The exercise dosage is also chosen based on the training objectives. The application of exercise doses will influence the expected variables. Exercises for weight loss are characterized by burning fat. There are options in determining the exercise dose for weight loss. This study aimed to compare the 75% and 100% exercise intensity doses to fluctuations in weight loss. This study does not focus on the press and post-test alone, but rather on proving how effective it is between 75% and 100%. Experimental research design provides 75% treatment of circuit training with 100% weights and circuits. The research was conducted on 12 students as a sample. Exercises are performed using 12 tools. Before and after exercise, weigh the body. Based on the recording during exercise, it turns out that the bodyweight will decrease more if you use a higher intensity (100%) with a mean value of 0.3113 and 0.2592, based on the normality test, it turns out that the data is not normal. Non-parametric analysis with Wilcoxon W has a significance value of 0.033, so it can be concluded, first, that 75% and 100% intensity affects the weight loss after exercise, that there is a difference between the two intensities with 100% more effective intensity.